The impact of the global financial crisis on business cycles in Asian emerging economies - Jarko Fidrmuc; Iikka Korhonen (Center for Economic Studies and ifo Institute (CESifo), 2009)
We analyze the transmission of global financial crisis to business cycles in China and India. The pattern of business cycles in emerging Asian economies generally displays a low degree of synchronization with the OECD countries, which is consistent with the decoupling hypothesis. By contrast, however, the current financial crisis has had a significant effect on economic developments in emerging Asian economies. Applying dynamic correlations, we find wide differences for different frequencies of cyclical development. More specifically, at business cycle frequencies, dynamic correlations are typically low or negative, but they are also influenced most by the global financial crisis. Finally, we find a significant link between trade ties and dynamic correlations of GDP growth rates in emerging Asian countries and OECD countries.
Keywords: E32; F15; F41; 330; financial crisis; business cycles; decoupling; trade; dynamic correlation; Finanzmarktkrise; Makroökonomischer Einfluss; Konjunkturzusammenhang; Aufstrebende Märkte; Asien; OECD-Staaten